Partisipasi Politik Perempuan Islam Indonesia Dalam Tradisi “Nu” - Erni Isnaeniyah (UIN Sunan Gunung Djati Bandung, 2017)
This journal explores the role of women when incorporated in Indonesian Islamic women's organization called NU's. This organization contributes a lot to the development of women in Indonesia, particularly concerning social welfare society internally as well as externally. Such as overcoming problems of underage marriage is a national issue that must be resolved. Through the participation of leaders of the Moslem according to its level in the Advisory Board of Marriage and Divorce Settlement. The implications are shown which gives the changes in the educational aspects that depict women in Indonesia in order to compete, health, religious, also active in government agencies such as participating formulate laws as the aspirations of the people's voice (DPR) also at the same time women's organizations this was also able to open communist group in Indonesia.